Influence of metal resistant-plant growth-promoting bacteria on the growth of Ricinus communis in soil contaminated with heavy metals - Rajkumar, Mani (2008)
The metal resistant-plant growth-promoting bacterial (PGPB) strains PsM6 and PjM15 isolated from a serpentine soil were characterized as Pseudomonas sp. and Pseudomonas jessenii, respectively, on the basis of their morphological, physiological, biochemical characteristics and 16S rDNA sequences. Assessment of plant growth-promoting parameters revealed the intrinsic ability of the strains for the utilization of 1-aminocyclopropane-1-carboxylic acid as the sole N source, solubilization of insoluble phosphate and production of indole-3-acetic acid (IAA). Further, a pot experiment was conducted to elucidate the effects of inoculating metal resistant PGPB on the plant growth and the uptake of Ni, Cu and Zn by Ricinus communis. Inoculation of Pseudomonas sp. PsM6 or P. jessenii PjM15 increased the shoot and root biomass of R. communis grown in non-contaminated and contaminated soil. However, the maximum biomass was observed in the plants inoculated with strain PjM15. This effect can be attributed to the solubilization of phosphate and production of IAA. Inoculation of Pseudomonas sp. PsM6 and PjM15 did not greatly alter the organ metal concentrations except Zn which concentration was higher in root, stem and leaf of inoculated plants. The results of metal extraction with PGPB strains showed that PsM6 was more efficient at solubilizing Zn than PjM15, and that PjM15 was better at solubilising Ni and Cu than PsM6. Owing to its wide action spectrum, the metal resistant PGPB could serve as an effective metal sequestering and growth-promoting bioinoculant for plants in metal-stressed soil. The present study has provided a new insight into the phytoremediation of metal-contaminated soil.